The Effectiveness of Health Education in Increasing Knowledge of Non-Communicable Disease Prevention among Housewives - Nabila Aulia Tsaqifah; Ainina Al Shadrina; Mailani Dwi Hidayati; Dwi Wydiawati; Ghea Farmaningthias Putri; Rifda Hanifah (Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
Non-communicable diseases (NCDs) represent a growing public health burden globally and nationally, highlighting the need for community-based preventive interventions. This study aimed to evaluate the effectiveness of a health education program in improving knowledge of NCD prevention among housewives in Serang Regency, Banten. A one-group pre-test–post-test design was conducted among 29 housewives recruited from a religious study group in Bulakan Village, Serang Regency, in January 2026. The intervention consisted of a mini-lecture supported by visual presentations on NCD risk factors and healthy lifestyle practices, complemented by blood pressure screening to promote early detection of hypertension and increase participants' awareness of their health status. Knowledge was assessed using structured pre- and post-test questionnaires, and the results were analyzed descriptively by comparing participants' knowledge levels before and after the intervention. Before the intervention, 46% of participants had poor knowledge, while only 18% demonstrated very good knowledge. After the intervention, the proportion of participants with very good knowledge increased to 69%, representing a 51-percentage-point improvement, while the proportion with poor knowledge decreased from 46% to 13%, a reduction of 33 percentage points. The blood pressure screening also enabled participants to recognize their current blood pressure status and reinforced the importance of routine health monitoring as part of NCD prevention. In conclusion, community-based mini-lecture health education combined with blood pressure screening effectively improved knowledge of NCD prevention and strengthened community awareness of early NCD risk detection. Empowering housewives as family health decision-makers can support sustainable community-based health promotion initiatives, including the Healthy Living Community Movement (GERMAS).